Walt Disney's Pinocchio - Fletcher, Steffi; Collodi, Carlo 1826-1890; Dempster, Al (New York Golden Books, 2008)
The adventures of the wooden puppet boy whose nose grew whenever he told a lie
English stories
1 2
Keywords: Fairy tales; Puppets -- Fiction